Resilient nekton composition in the face of climate‐driven foundation species shifts - Herbert Leavitt; Alexander Thomas; Jennifer C. Doerr; David S. Johnson; James A. Nelson (Ecology, 2026)
Climate‐driven range expansions of individual species are well‐documented, but corresponding community shifts are not. This lack of widespread community change may indicate communities can resist wholesale change with the arrival of new species. In the northern Gulf of Mexico, climate change is driving the expansion of black mangroves ( Avicennia germinans ) into areas traditionally dominated by smooth cordgrass ( Spartina alterniflora ). This study investigates the effects of these changes on the species composition of animals and habitat structure in Louisiana, USA, with implications for how species expand their range under shifting climactic regimes. Using quantitative nekton sampling and satellite imagery analysis over two decades, we observed a substantial increase in winter temperatures of 3.5°C and a regime shift from marsh to mangrove habitats. Despite these remarkable environmental changes, the composition of nekton remained stable. We expected that warming temperatures and the expansion of black mangroves would shift nekton community composition in our system by favoring warm‐adapted species and facilitating the arrival of new climate migrants. However, based on the community temperature index and species‐level analysis of relative abundances, thermal tolerance, and latitudinal range, we found no detectable increase in thermal affinity or establishment of new warm‐adapted taxa in Port Fourchon since 2002. Given that many systems experiencing comparable climate forcing have undergone marked compositional shifts, our findings suggest that local biotic interactions and species adaptability may buffer this community from the broader range expansions observed elsewhere. Our findings highlight the resilience of estuarine communities to rapid environmental changes and emphasize the need for further research on the indirect effects of habitat shifts on food web dynamics.

Exploitation Drives Changes in the Population Connectivity of Queen Conch (Aliger gigas) - Ana C. Vaz; Mandy Karnauskas; Claire B. Paris; Jennifer C. Doerr; Ronald L. Hill; Calusa Horn; Margaret H. Miller; Melissa Neuman; Kevin J. McCarthy; Nicholas A. Farmer (Frontiers in Marine Science, 2022)
The queen conch , Aliger gigas , is an endemic and iconic marine gastropod of the Wider Caribbean region that has been harvested for thousands of years. Conch are slow-moving and require contact to mate; overfishing has reduced populations in many areas compromising its rates of reproduction. Long-range dispersal and mixing between distinct populations occur in the queen conch’s early life history stages, when pelagic larvae are transported by oceanic currents. Genetic studies suggest that gene flow between populations decreases as the distance between populations increases. Here, we assessed how the population connectivity of conch changes with spatially variable patterns of fishing exploitation by simulating larval dispersal and comparing the potential connectivity under an unexploited and a contemporary exploited reproductive scenario. Results demonstrate that reduced egg production, due to heterogeneous fishing pressure and localized depletion, significantly alters population connectivity patterns as well as the structuring of populations and metapopulations across the species’ range. This strongly suggests that estimates of contemporary demographic rates, together with estimates of reproductive output need to be included in population connectivity studies. The existence of self-sustained metapopulations of queen conch throughout the Wider Caribbean suggests that replenishment through larval dispersal occurs primarily within sub-regional spatial scales, emphasizing the need for regional and local conservation and management measures to build and protect reproductively active populations and nursery habitat across multiple jurisdictions.

Foundation Species Shift Alters the Energetic Landscape of Marsh Nekton - J. Mason Harris; W. Ryan James; Justin S. Lesser; Jennifer C. Doerr; James A. Nelson (Estuaries and Coasts, 2021)

Population dynamics and genotypic richness of threatened Acropora species and their hybrid in the U.S. Virgin Islands - Hannah F. Nylander-Asplin; Ronald L. Hill; Jennifer C. Doerr; Lisa Greer; Nicole D. Fogarty (Coral Reefs, 2021)
Acropora cervicornis and A. palmata have experienced substantial losses in coral cover throughout the Caribbean, but their hybrid ( A. prolifera ) appears to be increasing at some sites. The shifts in relative abundance could result from hybridization with subsequent asexual fragmentation, recent increased hybridization, or a disproportionate loss in the parental species. Here, acroporid taxa from three U.S. Virgin Islands sites were genotyped revealing 35 hybrid genotypes, suggesting multiple hybridization events. Genotypic richness in A. cervicornis (0.62), A. prolifera (0.64), and A. palmata (0.68) was not significantly different across sites. To further explore acroporid dynamics at these sites, we analyzed existing photo transects from 2009 to 2017 to reveal significant losses of A. cervicornis but stable hybrid percent cover. High genotypic richness and stable populations suggest acroporid hybrids may become the primary shallow reef-builders in some locations previously occupied by the parental species.

Salinity Selection by Juvenile Brown Shrimp (Farfantepenaeus aztecus) and White Shrimp (Litopenaeus setiferus) in a Gradient Tank - Jennifer C. Doerr; Hui Liu; Thomas J. Minello (Estuaries and Coasts, 2016)